Making It Count: Pilgrimage and the Enumeration of Publics - Simon Coleman (Religions)
An activity that is widespread but rarely closely examined in studies of pilgrimage is the enumeration of pilgrims (and related visitors) to shrines and their environs. Such “biopolitics of hosting” can play a significant role in mobilising the religious imagination of shrine administrators, especially in contexts of apparently growing secularity. Number can be deployed by professional hosts to represent undifferentiated visiting publics in terms of spiritual possibility. In these terms, precision in statistics is likely to be less useful than figures that can be viewed through a distanced lens of potentiality. These ideas are developed through an examination of the Christian pilgrimage site of Walsingham, in eastern England.